Financing Public Transit Systems In Kuala Lumpur: Challenges And Prospects - Amin Tamale Kiggundu (Indonesian Journal of Geography, 2008)
Prioritizing public tramjport in large cities requires huge amount of money.In Kuala Lumpur for example, public transport services are relatively poor and inefficient due in part to the inability by the major operators to mobilize ample investment capital. Besides, the new funding systems such as the Public Transportation Trust Fund (PTTF) may not be able to solve the problem because they are still unclear and incoherent. Other key challenges are: lack of a pro-transit policy. rapid motorization. urban decentralization as well as dependence on farerevenue and banks to fund new investments. CrucianF. due to the poor design of private rail concessions, government intervention has been inevitable.